Back Cover: Nature and Topology of Metal–Oxygen Binding Sites in Zeolite Materials: 17O High‐Resolution EPR Spectroscopy of Metal‐Loaded ZSM‐5 (Angew. Chem. Int. Ed. 36/2019). Issue 36 (23rd August 2019) - Morra, Elena; Signorile, Matteo; Salvadori, Enrico; Bordiga, Silvia; Giamello, Elio; Chiesa, Mario
Abstract : The nature of the chemical bonding of open‐shell metals in zeolites is revealed through the combination of site‐selective 17 O isotopic labeling and electron paramagnetic resonance spectroscopy. In their Communication on page 12398 ff., M. Chiesa and co‐workers provide details of the metal–oxide interaction, including covalency, ionicity, and electron and spin delocalization, and translate these into a full atomistic model.